ENERGY TRANSITION – THE CHALLENGES FOR POLAND VERSUS THE EXPERIENCE OF EU MEMBER STATES - Marciniuk-Kluska, Anna; Ojdana-Kościuszko, Monika (Management and Administration Journal, 2024)
Energy security is essential for Poland’s economy, society and sovereignty. Its essence is to provide continuous access to energy, the amount of which is sufficient to meet our country’s needs regardless of possible disruptions or threats. The consequences of the war that Russia started in 2022 have reached far beyond the borders of Ukraine. Energy prices all over Europe have significantly increased, thus clearly showing that much more green energy needs to be produced. Renewable energy sources, including wind energy, are playing an important and positive role in curbing the energy price rise, which would have been even stronger had it not been for wind energy. The purpose of the paper is to prepare a forecast on the energy production from renewable energy sources with the use of predictive models based on function approximation. Wind energy production is uncertain and depends, among others, on atmospheric factors, such as the wind power. The conditions for generating electric energy and the price of final energy may deepen the discrepancies between the social and economic development of countries and contribute to the polarisation of the world.